Problematika Pendidikan Anak dalam Pengasuhan Institusional di Panti Asuhan Harapan Mandiri Makassar - Isa Fadillah; Irene Sampe; Naila Tul Zahra (Contemporary Education Review, 2026)
This study aims to analyze the educational dynamics of children living in the Harapan Mandiri Orphanage, Makassar, by highlighting the structural, motivational, and relational challenges that shape their learning processes. The research adopts a qualitative approach using a case study strategy within a constructivist–interpretive paradigm. Data were collected through in-depth interviews, observation, and documentation involving 15 informants, consisting of 10 orphanage children and 5 caregivers. The findings reveal three main issues. First, there is a mismatch between grade placement and children’s academic abilities, which contributes to low self-confidence, learning gaps, and the risk of school dropout. Second, children’s learning motivation is shaped by social stigma and limited academic support, leading some of them to perceive education instrumentally as a means of survival. Third, limited emotional relationships and the weak internalization of educational values within the orphanage result in a mechanical rather than meaningful character-building process. These findings indicate that educational challenges faced by children in orphanages are not merely individual problems but are shaped by the interaction between resource constraints, weak institutional coordination, and limited psychosocial support.